Fighting in the Fightschools late XVth, early XVIth century - Jaquet Daniel (Acta Periodica Duellatorum, 2013)
This article discusses the role played by Fightmaster (master-at-arms, Schirm- or Fechtmeister ) in the Fightschools (Fechtschulen ) taking place in the swiss cities at the end of the middle ages. The strong link between these lessstudied events and the practice of martial arts according to the technical literature (Fechtbücher) will be examined, as well as the figure of the Fightmaster.